2017
DOI: 10.3390/v9100310
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Attachment Protein Contributes to Neutrophil Recruitment into the Airways of Infected Mice

Abstract: Human Metapneumovirus (HMPV) is a leading respiratory pathogen that causes lower respiratory tract infections worldwide. Acute HMPV infection induces an exacerbated inflammatory neutrophilic response leading to bronchiolitis and pneumonia. However, the mechanism by which the virus regulates neutrophil infiltration into the airways still remains unexplored. In this work, we used an experimental mouse model of HMPV infection to demonstrate that the attachment (G) protein of HMPV contributes to the recruitment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…HMPV shares with RSV the same ability to decrease IFN response, despite the lack of NS1 and NS2 proteins. It has been documented that HMPV-G protein has the ability to inhibit the IFN type 1 response in vitro and in vivo [38,39] and that its SH and M2-2 proteins can also modulate the host's immune responses [40][41][42]. Both HMPV and RSV can persist in the lungs of an infected animal host, despite the presence of neutralizing antibodies [34,43].…”
Section: Need For a Vaccinementioning
confidence: 99%
“…HMPV shares with RSV the same ability to decrease IFN response, despite the lack of NS1 and NS2 proteins. It has been documented that HMPV-G protein has the ability to inhibit the IFN type 1 response in vitro and in vivo [38,39] and that its SH and M2-2 proteins can also modulate the host's immune responses [40][41][42]. Both HMPV and RSV can persist in the lungs of an infected animal host, despite the presence of neutralizing antibodies [34,43].…”
Section: Need For a Vaccinementioning
confidence: 99%
“…Among these, the attachment or G glycoprotein has the function to recognize and promote the first interaction with the host ( 26 ). It has also been described that the G protein has the ability to inhibit the IFN-I response not only in vitro ( 17 ), but also in an in vivo model ( 27 ). The latter study showed that the G protein is associated with the recruitment of neutrophils into the alveolar space in lungs of mice infected with hMPV ( 27 ).…”
Section: Role and Effect Of The Hmpv-proteins In Avoiding The Immune mentioning
confidence: 99%
“…It has also been described that the G protein has the ability to inhibit the IFN-I response not only in vitro ( 17 ), but also in an in vivo model ( 27 ). The latter study showed that the G protein is associated with the recruitment of neutrophils into the alveolar space in lungs of mice infected with hMPV ( 27 ). The authors propose that this phenomenon is due to the inhibition of the IFN response, detecting important changes in molecules involved in the recruitment of neutrophils such as; CCL3, CCL4, VEGF, TNF, IL-17, and CXCL2 ( 27 ).…”
Section: Role and Effect Of The Hmpv-proteins In Avoiding The Immune mentioning
confidence: 99%
“…Several studies have shown that infection with different strains of HMPV induce a strong immune response characterized by production of interferons in vitro [ 57 , 86 , 87 , 88 , 89 ] or in vivo [ 57 , 88 , 90 , 91 , 92 , 93 ] ( Table 1 ). However, this response is contingent on viral replication as IFN induction is abolished in UV-inactivated HMPV infected cells [ 57 , 94 , 95 ] and in vivo [ 90 ].…”
Section: Induction Of Interferon By Hmpv Infectionmentioning
confidence: 99%
“…In fact, the G protein is implicated to have an inhibitory effect on RIG-I mediated activation of type I IFN (IFN-α/β) production in airway epithelial cells [ 89 ] and in human moDC [ 105 ]. Furthermore, our laboratory has shown that the HMPV G protein also attenuates the activation and production of IFN-λ in vitro and in vivo [ 57 ] and that the release of IFN-α is also compromised in the airways of infected mice, by the effect of the G protein [ 90 ]. The protective immunogenicity properties exhibited by the rHMPVΔG virus makes it a potential vaccine candidate.…”
Section: Inhibition Of Ifn Response By Hmpvmentioning
confidence: 99%